RECONSIDER THE ‘ ADALAH OF MU’AWIYAH: Reviewing His Hadth Narrations In His Political Decisions - Syidik, Nur Aliman; Firdausy, Hilmy; Fatkhi, Rifqi Muhammad (Proceeding International Conference on Religion, Science and Education, 2025)
This paper is motivated by three ongoing discourses; 1) the discourse about re-evaluating the principle that all al-sahabah ‘udul in narrating hadiths based on their subjectivity when transmitting hadiths; 2) the influence of politics in hadith narration; and 3) the presence of negative narratives about Mu’awiyah. This research fills a gap in the study of the al-sahabah subjectivity by exploring the correlation between Mu’awiyah’s political power and his hadith narration. So, this research aims to reconsider the ‘adalah of Mu’awiyah ibn Abi Sufyan. This needs to be done to provide recommendations for action, if the discourse on reconsidering the ‘adalah of al-sahabah is undertaken. This paper is a qualitative research. The method used in this study is descriptive-analytical. The main object of the research is the hadiths narrated by Mu’awiyah, which are traced using the book Tuhfat al-Ashraf bi Ma’rifat al-Atraf to identify the hadiths of Mu’awiyah that are found in sahihayn. These hadith are analyzed in the context of Mu’awiyah political decisions. In conclusion, the data reveals that Mu’awiyah narrated hadiths on various themes including theology, worship, virtues, Sufism, law, and politics. Political-themed hadiths occupy the lowest percentage. The two of fifteen hadiths are relevant to his political policies. Mu’awiyah’s interests are mainly reflected in the interpretation of hadiths, where he transmitted the hadiths along with interpretations that benefited him. Furthermore, no hadiths contradict his political policies. The small percentage of politicization indicates that Mu’awiyah minimally used hadiths as a political tool. Therefore, this research supports the principle of al-sahabah kulluhum ‘udul fi al-riwayah and the study of the characteristics of al-sahabah is sufficient to be applied only in fahm al-hadith.